Prinsip Good Governance dalam Tata Kelola Dana Desa - Mutiara Elfionita; Titi Darmi; Faizal Anwar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of the study was to find out how the Good Governance Principles in Village Fund Governance in Padang Capo Ulu Village, Lubuk Sandi District, Seluma Regency. The research method uses a qualitative description approach. Research data sourced from primary and secondary data. Data collection techniques through in-depth interviews, field observations, and photo documentation. The principles of Good Governance in this study are seen from the indicators of participation, transparency and accountability. The results of the study indicate that the 3 principles of good governance in the management of the Village Fund have been running in accordance with the mandate of the legislation. The conclusion of this research is that the transparency of village funds and management has been going well, with deliberation to discuss the management of village funds. Keywords: Governance, Remote Village, Village Development, Village Fund